Mindful makers: Question prompts to help guide young peoples' critical technical practices in maker spaces in libraries, museums, and community-based youth organizations - Bowler, Leanne; Champagne, Ryan (Library & information science research, 2016)
This study examines question prompts as a means to scaffold reflection and reflexivity in the design, development, and use of technological artifacts in maker spaces for youth at public libraries, museums, and community-based organizations. Qualitative analysis is applied to data gathered in four focus groups with teens, three semi-structured interviews with adults who facilitate maker spaces, and six observation sessions. Outcomes include a rich description of critical thinking in the context of technology practice, and secondly, a set of eight activation questions that serve as a tool kit to encourage reflection and scaffold mindful and critical practices in community-based maker spaces for youth. Results from this study support the development of nstruments and practices to support mindful making and critical technical practice in maker spaces for youth. •This research explores the use of question prompts to support reflection and reflexivity in maker spaces for youth.•Data were gathered at maker spaces at a public library, a children's museum, and a community organization serving teens.•Eight core question prompts for scaffolding critical technical practice are suggested.